Windfarms and residential property values - McCarthy, Iona; Balli, Hatice Ozer (International Journal of Strategic Property Management, 2014)
This study examines the effect that windfarm visibility has on residential property values using a hedonic regression model. The study area is Ashhurst, New Zealand, a township of approximately 900 dwellings. Ashhurst is located within eight kilometres of two separate windfarms that were developed between 1998 and 2007 comprising 103x660kW turbines, 31x3MW turbines, and 55x1.65MW turbines. The analysis uses the 945 open market house sales that occurred in Ashhurst between 1995 and 2008. Visual impact of turbines is studied to capture the impact of windfarms and it is assessed using GIS viewshed analysis and by field inspection. The hedonic models had satisfactory explanatory performance and in each case indicated that the turbines located between 2.5 and 6 kilometres from the township of Ashhurst had no significant impact on property value.First Publish Online: 20 Jun 2014